2011
DOI: 10.1007/s00011-011-0407-5
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania (Viannia) shawi purified antigens confer protection against murine cutaneous leishmaniasis

Abstract: The capability of antigens to restrain IL-4 levels and increase IFN-γ was associated with protection, such as in immunization using F1 antigen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The findings of this study provide a warning for the possible association between L. (V.) shawi and mucous lesions, since L. (V.) braziliensis can be found both in normal mucosa and in injured mucosa [5]. Experimental studies showed that infection by L. (V.) shawi without symptoms in mice can occur through the activation of antigens capable of inducing a protective immune profile, which is important for the development of vaccines against TL [34,35]. These observations allow for further studies in the fields of genomics and bioinformatics in this species of Leishmania.…”
Section: Discussionmentioning
confidence: 77%
“…The findings of this study provide a warning for the possible association between L. (V.) shawi and mucous lesions, since L. (V.) braziliensis can be found both in normal mucosa and in injured mucosa [5]. Experimental studies showed that infection by L. (V.) shawi without symptoms in mice can occur through the activation of antigens capable of inducing a protective immune profile, which is important for the development of vaccines against TL [34,35]. These observations allow for further studies in the fields of genomics and bioinformatics in this species of Leishmania.…”
Section: Discussionmentioning
confidence: 77%